The Authenticity and Social Distance Effect on Motivation of Corporate Social Responsibility and Implication on Company Image on PT Amerta Indah Otsuka, Pasuruan - Indonesia - Mohammad Syaifuddin Ali Sahidu; Grahita Chandrarin; Suriptono Suriptono (International Conferences SDGs 2030 Challenges and Solutions, 2030)
Purpose - This study aims to describe Authenticity, Social Distance, CSR Motivation andCompany Image. This study also analyzed the effect of Authenticity on CSR Motivation,analyzed the influence of Social Distance on CSR Motivation and analyzed the influence ofCSR Motivation to Company Image PT Amerta Indah Otsuka, Kejayan PasuruanThe research design - The research design using causal research design, the population in thisresearch is the direct beneficiaries of Rumah Belajar and Posyandu program of PT AmertaIndah Otsuka, Kejayan Pasuruan consists of parents / guardians of the participants of RumahBelajar, elementary school teachers participated in Rumah Belajar of AIO, And Posyanduofficers, as well as the village Pacarkeling district Kejayan Pasuruan. The analytical techniqueuses path analysis.Findings - Based on the results of the analysis show that authencity is formed from indexicaland iconic, the main contribution of authenticity formation is indexical. Social Distance isformed from Objective Social Distance and Subjective Social Distance, the main contribution ofsocial distance formation is Objective Social Distance. CSR motivation is formed fromCorporate Charity, Corporate Philanthropy and Corporate Citizenship, the main contribution ofCSR motivation is Corporate Philanthropy. Company Image formed from Personality,Reputation, Value and Corporate Identity, the main contribution of establishment of companyimage is Corporate Identity. Authenticity has a significant effect on CSR Motivation, SocialDistance has significant effect on CSR Motivation. Motivation of CSR has a significant effecton company image of PT Amerta Indah Otsuka, Kejayan Pasuruan.Renewal - This study is the application of findings in previous research (2016) to directstakeholders and linked the influence of CSR motivation to company image. Keywords:authenticity, social distance, motivation CSR, company Image, Otsuka